Construction of Virtual Neuron and Consolidation of Sleep and Memory Process– A Molecular Docking and Biomathematical Approach - Zhao Bin; Cao Jinming; Huang Kuiyun; Jiang Xia; Tang Jingfeng (Journal of Model Based Research, 2019)
This methods paper combines molecular docking and biomathematical modeling to construct a virtual neuron framework for studying sleep‑related memory consolidation. It outlines model components and validation approach.
Keywords: Virtual Neuron